Facebook marketing for dummies - Haydon, John (--For dummies., 2013)
The bestselling book updated with all of the latest features and Facebook upgrades This latest revision covers the newest Facebook tools and techniques, including how to use the Timeline for your business page and how to take advantage of third-party apps. It will also explore the psychology of the Facebook user, explain ways to build your fan base and increase brand awareness, look at how to promote your page with events and contests, and discuss ways to monitor and measure your efforts. Real-world case studies illustrate the techniques. Facebook is among the most important.